2008
DOI: 10.1159/000111990
|View full text |Cite
|
Sign up to set email alerts
|

Metabolically Engineered Yeasts: ‘Potential’ Industrial Applications

Abstract: Industrial biotechnology and metabolic engineering can offer an innovative approach to solving energy and pollution problems. The potential industrial applications of yeast are reviewed here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 94 publications
(43 reference statements)
0
20
0
1
Order By: Relevance
“…Saccharomyces cerevisiae is a unicellular yeast and one of the most explored organism in terms of industrial applications and genetic studies [8]. Several previous studies showed that members of Saccharomyces genus can possess anti-bacterial and probiotic properties [9].…”
Section: Introductionmentioning
confidence: 99%
“…Saccharomyces cerevisiae is a unicellular yeast and one of the most explored organism in terms of industrial applications and genetic studies [8]. Several previous studies showed that members of Saccharomyces genus can possess anti-bacterial and probiotic properties [9].…”
Section: Introductionmentioning
confidence: 99%
“…The yeast Saccharomyces cerevisiae is an organism that is able to grow at low pH values (38), although it does not naturally produce fumaric acid. Additional advantages of this organism are that its genome has been fully sequenced and that it is considered by the American Food and Drug Administration (FDA) as an organism generally regarded as safe (GRAS) (6). In addition, in several recent studies, the yeast S. cerevisiae has been proposed as a cell factory for the production of bulk chemicals, such as malic, lactic, and citric acid from renewable substrates (1,30,36,42,43).…”
mentioning
confidence: 99%
“…Jüngste Aufmerksamkeit gilt der L-Milchsäure als Ausgangsmonomer für den biologisch abbaubaren Kunststoff Polylactid (PLA). Aufgrund des wachsenden Marktes für Polymilchsäure und der Erschließung neuer Einsatzmöglichkeiten wird die derzeitige Produktion von etwa 250 000 Jahrestonnen Milchsäure deutlich steigen [4]. Seit 1895 wird MS überwiegend biotechnologisch hergestellt, da die MS annähernd optisch rein produziert werden kann, was für die Dilactidsynthese zur Produktion von PLA von Bedeutung ist.…”
Section: Einleitung Und Problemstellungunclassified